Os pronomes: uma classe de palavras léxico-gramaticais em retrospectiva - Araujo, Wagner Santos (2007)
The Dissertation is within the History Research Line and Description of the Portuguese Language/Post-Graduation Studies Program in Portuguese Language-PUCSP and focuses, by means of a historiography perspective, on the class of pronouns as object of the investigation, guided by the presupposition according to which the relationship between structure and linguistic function is inseparable: if there is a variation in the structure, then there is a variation in the function. The history of linguistics was the beginning point, whose grounds were the support for the building of the Greek and Latin grammar, extending them up to the current times, as the general purpose was aimed at the understanding of exposures or descriptions that enabled the understanding of the pronoun as a lexical and grammatical class, that is, in regards to its structure and functioning. In order to measure this general purpose, three specific objectives were established in view of the pronouns, in different stages of the building of the Traditional Contemporaneous Grammar, which became Normative in view of the creation of a model of linguistic policy, instituted by the Greek Estate. The first purpose focused on the treatment given to the pronouns by the Grammar of the Word; the second, by the Grammar of the Sentence, and the third, by the Descriptive or Scientific Grammar. The results presented in Chapter I guided the development of Chapters II and III: the non-dissociation between the units of the lexicon and its relationships, of morphosyntatic-semantic character, is the matrix by means of which the pronouns should be described, as the languages are classified in that manner. In this way, the pronouns are empty words, grammatical elements, whose contents come from the anaphoric relationship that they establish with the name they replace. This substitutive relationship needs to be seen by that one established between the name and the verb; as the content of the pronominal forms emerges from that relationship as an amalgam, which, by replacing the name in its relationship with the verb, binds the content of both of them - proposition conceived by Apolônio Díscolo for whom the pronoun was a paranonímia synonymy and a semiosis. It is evidenced that this presupposition contemporaneously retaken by the Speech Analysis, whose grounds are circumscribed to the theory of the enunciation got lost in the grammatical descriptions, although the Normative Grammar has been continuously re-contextualized. By means of this movement it continues being traditional in the innovation of the scientific advancements in the language field. Resulting from this process of reinterpretation of the past by the present, it extends the description centered in the word to the sentence, grounded on investigations of medieval philosophers and the taxonomic systematization of the substantive pronouns and the adjectives. However, the only grammars who focus on the pronouns because of their deictic and anaphoric functions are Evanildo Bechara Normative Grammar and Lucién Tesniére Dependency Grammar or Functional, enabling the assurance that these are the matrixes of the textual cohesion process: the voice of Apolônio in the modern times, the dialogue that allows the recognition of what is old in what is new